Does Electroencephalography Result Affect the Success of Treatment for Epilepsy Patients ? - Sri handayani Suroto; Yunni Diansari; Selly Marisdina; Nova Lestari; Sri Yani (HM Publisher, 2021)
A B S T R A C TIntroduction: Approximately there is 50 million people with epilepsy in the world.Currently, pharmacological management is the most therapeutic option. However,about 30% of patients will develop drug-resistant epilepsy. Many factors arethought to affect the treatment success. This study was conducted to determinethe relationship between electroencephalographic results and epilepsy treatmentsuccess. Methods : This is cross sectional observational study. Inclusion criteriawas epileptic patients aged > 18 years and had received epilepsy treatment for atleast 1 year. The chi-square test is performed to see the relationship betweenresearch variables. Results: EEG results has an effect on the success of therapy(p 0.027). The most common type of epileptiform abnormality is sharp waves. Themost epileptiform amplitude and location were 80 microvolts and in the temporallobe. Conclusion: There is a significant relationship between EEG abnormalitiesand the epilepsy treatment success.